Mortality predictions for Ireland, 2001–2015: cancers of the breast, ovary, and cervix and corpus uteri. (1st January 2006) - O'LORCAIN, P.; Comber, H.
Abstract : Linear and log-linear Poisson regression models of Irish breast, ovarian, and cervical and corpus uterine cancer mortality data for the years 1953–2000 were used to predict European age standardized mortality rates (EASMRs) per 100, 000 person years and numbers of deaths for the period 2001–2015. Rates for the whole population and for those under 65 are expected to fall from their current levels for breast and corpus uterine cancers but not for ovarian and cervical uterine cancers. EASMRs for postmenopausal women aged between 55 and 69 years are predicted to fall for breast, ovarian, and cervical and corpus uterine cancers. The continuing expansion of the Irish female population is the primary reason why the numbers of deaths arising from breast, ovarian, and cervical uterine cancer are predicted to increase in all of the above age groups. It is not exactly clear why the numbers of corpus uterine cancer deaths are expected to continue to decline, but it may be a matter of improvement in overall death-certificate coding or their diagnoses as cervical cancer deaths.